2018
DOI: 10.3168/jds.2017-13476
|View full text |Cite
|
Sign up to set email alerts
|

The cost-benefit of genomic testing of heifers and using sexed semen in pasture-based dairy herds

Abstract: Recent improvements in dairy cow fertility and female reproductive technologies offer an opportunity to apply greater selection pressure to females. This means there may be greater incentive to obtain genomic breeding values for females. We modeled the impact of changes to key parameters on the net benefit from genomic testing of heifer calves with and without usage of sexed semen. This paper builds on earlier cost-benefit studies but uses parameters relevant to pasture-based systems. A deterministic model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…Although still measured in years, a much shorter timeframe can be considered. Adopting similar reasoning to Calus et al (2015) but modelling Australian dairy farms, Newton et al (2018) showed that the net benefit of genotyping to guide heifer-replacement decisions on an 'average' farm with surplus heifer-replacement candidates is likely to be positive. They found that when the selection decisions were based on parent average-derived EBVs, the net benefit of genotyping was AU$204 in a 100-cow herd in a scenario where all female progeny are tested.…”
Section: Timeframe For Valuationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although still measured in years, a much shorter timeframe can be considered. Adopting similar reasoning to Calus et al (2015) but modelling Australian dairy farms, Newton et al (2018) showed that the net benefit of genotyping to guide heifer-replacement decisions on an 'average' farm with surplus heifer-replacement candidates is likely to be positive. They found that when the selection decisions were based on parent average-derived EBVs, the net benefit of genotyping was AU$204 in a 100-cow herd in a scenario where all female progeny are tested.…”
Section: Timeframe For Valuationmentioning
confidence: 99%
“…Ultimately, the financial returns from genotyping to support replacement decisions are greatly influenced by individual farm parameters such as replacement rate, reproductive performance and current selection practices. However, being able to show that investments in herd improvement tools can be recouped within a short timeframe may support uptake of commercial genomic testing of heifers (Newton et al 2018).…”
Section: Timeframe For Valuationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar in concept to precision therapeutic treatments in humans, which is beginning to be used in the treatment of certain cancers by genotyping the cancer cells and adjusting the treatments accordingly (Leão and Ahmed, 2019). An example of this approach in livestock has already been implemented in dairy cattle, where separate genetic merits for cheese making (Francesco Tiezzi, 2018) and pasture-managed dairy cattle (Newton and Hayes, 2018) have been developed. Aside from this example, precision management based on genotype is still in its infancy.…”
Section: Science To Practicementioning
confidence: 99%
“…The use of sexed semen has been traditionally recommended only for heifers [18,19], as pregnancy rates are reduced in cows [20,21]. Although its usage is low (< 5%) within the AI market [22], it generates herd replacements and additional heifers [23].…”
Section: The Use Of Sexed Semen Helps Twin Prevention Strategiesmentioning
confidence: 99%